Financial networks and the globalization of transnational corporations: the case of educational services - Hall, Sarah (Oxford University Press, 2015)
In this article, I advance understandings of the intersection between financial and educational services from an economic geographical perspective by examining the importance of financial networks in shaping the internationalization activities of for- profit business education service firms. By combining relational approaches to the globalization of transnational corporations (TNCs) with work on monetary networks I argue that extra-firm networks with financial services are an important element in understanding how, where and why business education service firms internationalize. Theoretically, this argument responds to calls for firm finances to be more fully incorporated into understandings of wider economic geographies and, in particular, addresses the neglect of finance in extant understandings of the internationalization of TNCs. Empirically, I position educational services as an overlooked business services sector that deserves greater attention within economic geography.